Outcomes of Congenital Nasolacrimal Duct Obstruction Surgery Converted into Balloon Dilation and Silicone Intubation due to Probing Difficulty - Oren Yaakov Sagiv; Achia Nemet; Asaf Achiron; Doron Neumann; Raimo Tuuminen; Oriel Spierer (Journal of Ophthalmology)
Background. To report the outcomes of balloon catheter dilatation and silicone intubation as a sequential secondary surgery under the same anesthesia, a stepwise approach for congenital nasolacrimal duct obstruction (NLDO) when probing and irrigation as primary procedure fails. Methods. A retrospective study included children with NLDO who underwent probing and irrigation only, and those who underwent in the same surgery under anesthesia, adjunct balloon catheter dilation and silicone intubation due to difficulty of the probe passage or fluid regurgitation from the punctum. The primary outcome was surgical success defined as resolution of preoperative symptoms and signs at 1 month. Results. A total of 105 NLDO cases were included. Eighty-four cases underwent probing and irrigation only, whereas 21 cases required balloon dilation and silicone intubation consecutively after the first procedure. Patient age at surgery was higher for those requiring balloon dilatation and intubation (30.3 ± 8.0 months) when compared to those with probing and irrigation only (22.4 ± 10.3 months, p<0.001). The onset of symptoms, preoperative clinical findings regarding tearing and discharge and gender distribution of patients were comparable between the two groups. During the follow-up, the overall success rate for probing and irrigation only was 76.2% (64 out of 84 cases) and for balloon dilatation and silicone tube intubation was 90.5% (19 out of 21 cases). Conclusions. The surgical team may prepare to proceed with secondary surgery under the same anesthesia after the initial attempt of probing and irrigation. This stepwise two-stage approach in patients with congenital NLDO failing primary surgery resulted in a high success rate with minimal interventions, avoiding repeated general anesthesia.